Reducing West Nile Virus Risk Through Vector Management - Nasci, Roger S.; Mutebi, John-Paul (Journal of medical entomology, 2019)
Over 50,000 human West Nile virus (WNV) (Flaviviridae: Flavivirus) clinical disease cases have been reported to the CDC during the 20 yr that the virus has been present in the United States. Despite the establishment and expansion of WNV-focused mosquito surveillance and control efforts and a renewed emphasis on applying integrated pest management (IPM) principles to WNV control, periodic local and regional WNV epidemics with case reports exceeding 2,000 cases per year have occurred during 13 of those 20 yr in the United States. In this article, we examine the scientific literature for evidence that mosquito control activities directed at either preventing WNV outbreaks or stopping those outbreaks once in progress reduce WNV human disease or have a measurable impact on entomological indicators of human WNV risk. We found that, despite a proliferation of research investigating larval and adult mosquito control effectiveness, few of these studies actually measure epidemiological outcomes or the entomological surrogates of WNV risk. Although many IPM principles (e.g., control decisions based on surveillance, use of multiple control methodologies appropriate for the ecosystem) have been implemented effectively, the use of action thresholds or meaningful public health outcome assessments have not been used routinely. Establishing thresholds for entomological indicators of human risk analogous to the economic injury level and economic thresholds utilized in crop IPM programs may result in more effective WNV prevention.
Keywords: Mosquito-borne disease; Public health entomology; West Nile virus; Mosquito control; IPM